Inverted repeat nucleotide sequences in the genomes of Marek disease virus and the herpesvirus of the turkey. - Cebrian, J (1982)
The DNAs of two herpesvirus, the oncogenic Marek disease virus and the serologically related herpesvirus of the turkey, were studied by electron microscopy. On the basis of fold-back molecules observed in single-stranded DNA from both viruses, structures have been derived from the overall nucleotide sequence arrangement in their genomes. Although differing in molecular weight, the genomes of Marek disease virus and turkey herpesvirus are both constructed according to the same plan--two regions of unique nucleotide sequence, each enclosed by inverted repeat sequence. The genome structure of these viruses therefore closely resembles that of herpes simplex virus rather than the biologically more similar herpesvirus Epstein--Barr virus, H. saimiri, and H. ateles.